The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2139/ssrn.2338441
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and Low-Wage Mobility

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is no surprise then that having an internal locus of control has been linked with higher earnings (e.g., Heineck and Anger 2010;Piatek and Pinger 2010;Semykina and Linz 2007;Osborne Groves 2005;Osborne 2000;Goldsmith et al 1997;Duncan and Dunifon 1998;Andrisani 1977Andrisani , 1981, faster earnings growth (Schnitzlein and Stephani 2013), and greater job satisfaction (Ng et al 2006). Job seekers with an internal locus of control also have a higher probability of reemployment and shorter unemployment durations following job loss (Gallo et al 2003;Uhlendorff 2004).…”
Section: On the Importance Of Being Internalmentioning
confidence: 99%
“…It is no surprise then that having an internal locus of control has been linked with higher earnings (e.g., Heineck and Anger 2010;Piatek and Pinger 2010;Semykina and Linz 2007;Osborne Groves 2005;Osborne 2000;Goldsmith et al 1997;Duncan and Dunifon 1998;Andrisani 1977Andrisani , 1981, faster earnings growth (Schnitzlein and Stephani 2013), and greater job satisfaction (Ng et al 2006). Job seekers with an internal locus of control also have a higher probability of reemployment and shorter unemployment durations following job loss (Gallo et al 2003;Uhlendorff 2004).…”
Section: On the Importance Of Being Internalmentioning
confidence: 99%
“…6 The link between a positive attitude and the likelihood of progression has been highlighted by D’Arcy and Hurrell (2014). Optimism is, moreover, considered to be related to individuals’ locus of control (Klein and Helweg-Larsen, 2002; Ng et al, 2006), which has been shown to have an impact on mobility from low to higher pay (Schnitzlein and Stephani, 2016).…”
Section: Methodsmentioning
confidence: 99%